The South Shetland Islands, Antarctica: Lithostratigraphy and geological map - Bastías, Joaquín; Chew, David; Villanueva, Camila; Riley, Teal; Manfroi, Joseline; Trevisan, Cristine; Leppe, Marcelo; Castillo, Paula; Poblete, Fernando; Tetzner, Dieter; Giuliani, Gregory; López, Bastián; et al. (Frontiers in Earth Science, 2023)
Over the last few decades, numerous geological studies have been carried out in the South Shetland Islands, which have greatly contributed to a better understanding of its geological evolution. However, few attempts have been conducted to correlate the geological units throughout this archipelago. We present herein a review of the literature available in the South Shetland Islands, which we use to propose a lithostratigraphical correlation that constitutes a coherent stratigraphy for the main Mesozoic and Cenozoic rocks of the South Shetland Islands along with a new geological map. The lithostratigraphical correlation shows that the geological and environmental evolution comprises three main stages: 1) deep marine sedimentation from ∼164 to 140 Ma, 2) subaerial volcanism and sedimentation with a proliferation of plants and fauna from ∼140 to 35 Ma and 3) glacial and interglacial deposits from ∼35 Ma. The lithostratigraphical correlation also shows a broad geographical trend of decreasing age of volcanism from southwest to northeast, which has been previously suggested. However, this spatial age trend is disrupted by the presence of Eocene magmatism in Livingston Island, located in the centre of the archipelago. We suggest that the migration of volcanism occurred from the Late Cretaceous until the early Eocene. Subsequently, enhanced magmatic activity took place from the mid-Eocene until the Miocene, which we associate with processes related with the waning of subduction. Constraining the protolith age of the metamorphic complex of Smith Island remains challenging, yet holds key implications for the tectonic and accretionary evolution of the Antarctic Peninsula. The rocks recording the glaciation of this sector of Antarctica are well exposed in the northern South Shetland Islands and hold critical information for understanding the timings and processes that lead to the greenhouse to icehouse transition at the end of the Eocene. Finally, contemporaneous rocks to the breakup of Antarctic Peninsula from Patagonia that led to the opening of the Drake Passage and the development of the Scotia Sea are exposed in the centre and north of the South Shetland archipelago. Better constraints on the age and tectonic settings on these units may lead to further understanding the paleobiogeographical evolution of the region, which may have played an important role for speciation as a land bridge between South America and Antarctica. The dataset containing the geological map and associated information is shared as a shapefile or KML file.